2017
DOI: 10.1111/jar.12353
|View full text |Cite
|
Sign up to set email alerts
|

Physical and psychological health of family carers co‐residing with an adult relative with an intellectual disability

Abstract: Family carers of adults with intellectual disability appear to experience poorer health outcome than population norms. Adaption to the caregiving role may buffer negative outcomes. Further large scale, population-based, longitudinal research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 98 publications
4
44
0
Order By: Relevance
“…Chou et al () reported that younger caregivers reported a higher level of burden. Similarly, Grey et al () reported that caregiver age was the only variable significantly independently associated with caregiver burden, suggesting older age was associated with lower levels of burden, a finding also identified in this study. Grey et al () found that older caregivers experienced greater satisfaction with available supports and adopted active coping mechanisms that were associated with lower levels of burden and better health outcomes.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Chou et al () reported that younger caregivers reported a higher level of burden. Similarly, Grey et al () reported that caregiver age was the only variable significantly independently associated with caregiver burden, suggesting older age was associated with lower levels of burden, a finding also identified in this study. Grey et al () found that older caregivers experienced greater satisfaction with available supports and adopted active coping mechanisms that were associated with lower levels of burden and better health outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…Increased longevity has presented family caregivers with many challenges including increased care needs, failing health, ageing processes of their family member, financial concerns and worries for the future (Dillenger & McKerr, ; Schoufour, Evenhuis, & Echteld, ). In parallel, these caregivers are also ageing and may be experiencing both physical and psychological health problems (Grey, Totsika , & Hastings, ). Therefore, a growing population of ageing caregivers supporting adults with intellectual disabilities may be at risk of caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations